Hubungan Informasi Line Today dengan Pemenuhan Kebutuhan Informasi Mahasiswa - Laura Anggraeni Dhayuningrum; Prijana Prijana; Andri Yanto (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2017)
This study aims to find out whether there is a significant correlation between information in Line Today with the fulfillment of cognitive needs, affective needs, personal integrative needs, social integrative needs and escapist needs of students of Faculty of Communication Sciences Universitas Padjadjaran. This research method used the correlational quantitative method by using Pearson Product Moment. The main theory used in this research is information seeking from Donohew and Tipton. The population of this research was the active student of Faculty of Communication Sciences Universitas Padjadjaran who use Line and drawn sample with amount 150 using sample size, proportion of binomial, and sampling error table. The result shows that there is a significant correlation between information in Line Today with the fulfillment of cognitive needs, affective needs, personal integrative needs, social integrative needs and escapist needs of students Faculty of Communication Sciences Universitas Padjadjaran